Channel modelling using 5G for accurate positioning - Teo, Si Cheng (Nanyang Technological University, 2022)
Global Positioning System (GPS) is widely adopted throughout the world. It is a technology that is free and allows one’s positioning to be determined by the satellite. This technology, it has improved the quality of life of people as it is being used as a first choice for navigational purposes daily. However, GPS has its limitation, causing inaccuracy in positioning estimation. The two limitations are namely, the absence of the line-of-sight and multipath fading. These limitations are often common in our land-scarce Singapore, as the country has common attributes such as buildings and underground tunnels. Therefore, they are susceptible to these limitations. This project aims to tackle the accuracy of positioning estimation outdoors. With the usage of RSSI as the parameter, the project aims to develop a path loss model and algorithms to estimate a user’s position more accurately. The result of this project depicts the accuracy of RSSI as a parameter for positioning estimation.